Analysis Of Business Model Canvas (BMC) Of Lushwoods MSMEs - Vanessa; Tiurniari Purba (International Journal of Education Management and Religion, 2026)
: In Indonesia, the furniture MSME industry experienced a significant surge in performance in early 2025, with strong quarterly and annual growth. The Indonesian furniture industry demonstrated impressive performance, including in Batam. MSMEs in Batam have continued to grow year after year. Batam is a developed industrial city, and the furniture market opportunities in Batam are promising due to the city's rapid growth and strategic location, which supports domestic demand and export potential. Research objecctives: Based on the aforementioned opportunities, the purpose of this paper is to run an MSME business, namely Lushwoods furniture, using a Business Model (BMC) supplemented by a SWOT analysis. Proposed methods: This research is a qualitative study using a participatory approach, involving Lushwoods furniture MSMEs in the target area. The methods applied include: outreach, implementation workshops, mentoring, and evaluation. Result: The results indicate that partners who initially lacked business planning are now able to identify key elements of the BMC, manage resources, and develop marketing strategies and product diversification more effectively. Thus, the implementation of the BMC has proven effective in helping manage frozen food businesses more strategically and sustainably. Conclusions: The application of the canvas business model has proven effective in helping Lushwoods Furniture MSME manage its business in a more planned and strategic manner.